2021
DOI: 10.5935/1518-0557.20200109
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating response of D- Ribose-L-Cysteine on Sodium arsenate- induced hormonal imbalance, spermatogenesis impairments and histomorphometric alterations in adult male Wistar rat

Abstract: Objective: Reproductive toxicity is an important health challenge, mostly associated with exposure to several environmental toxicants. Arsenic is a ubiquitous toxic compound naturally present in the environment. This study was carried out to evaluate the dietary supplements of D-Ribose-L-Cysteine against sodium arsenate-induced testicular toxicity in adult male Wistar rats.Methods: A total of 32 male rats (150-250g) were randomly divided into four ( 4) groups (n=8). Group A received normal saline as placebo; G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Treatment with 200 mg/kg Vitamin E for 84 days increased spermatogenesis and restored blood LH, FSH, and testosterone levels [167], and improved semen quality in Teddy goat buck testicular tissue [200]. Oral administration of D-ribose-L-Cysteine at doses of 10 and 30 mg/kg over 28 days restored sperm count, motility, viability, LH, FSH, testosterone, and CAT, SOD, and GSH activities in rat testes [197]. In a recent study, nano vitamin C (NVC) was found to ameliorate arsenic-induced changes in testicular and sperm parameters.…”
Section: Other Phytonutrients That Promote Male Fertilitymentioning
confidence: 95%
“…Treatment with 200 mg/kg Vitamin E for 84 days increased spermatogenesis and restored blood LH, FSH, and testosterone levels [167], and improved semen quality in Teddy goat buck testicular tissue [200]. Oral administration of D-ribose-L-Cysteine at doses of 10 and 30 mg/kg over 28 days restored sperm count, motility, viability, LH, FSH, testosterone, and CAT, SOD, and GSH activities in rat testes [197]. In a recent study, nano vitamin C (NVC) was found to ameliorate arsenic-induced changes in testicular and sperm parameters.…”
Section: Other Phytonutrients That Promote Male Fertilitymentioning
confidence: 95%
“…Histological analyses of the ovary and the uterus were assessed from 5 μm sections of paraffin-embedded tissues following hematoxylin-eosin staining [ [61] , [62] , [63] ]. Histomorphological changes were assessed on microphotographs using a Scientico STM-50 microscope equipped with a Celestron MA411101 camera connected to a computer where the image was transferred and analyzed with the Image J1.3 software.…”
Section: Methodsmentioning
confidence: 99%
“…The hormonal levels of Testosterone (TT), Follicle Stimulating Hormone (FSH) and Luteinizing Hormone (LH) were measured using available immunoassay (ELISA) kits (Randox Laboratories Ltd, Admore Diamond Road, Crumlin, Co., Antrim, United Kingdom, Qt94QY) according to manufacturer instructions, following the method of Ogunlade et al (2021).…”
Section: Hormone Determinationmentioning
confidence: 99%